Comparison of newly diagnosed COPD patients and the non-COPD residents in Shanghai Minhang District - Yin, Xin; Zheng, Zixuan; Dong, Yue; Li, Junqing; Yang, Shuang; Xu, Qian; Hou, Shanshan; Zang, Yi; Ding, Heyuan; Xie, Juan; Jie, Zhijun; Jiang, Qingwu; et al. (Frontiers in Public Health, 2023)
Background To compare whether the general population, especially those without characteristic symptoms, need spirometry screening for chronic obstructive pulmonary disease (COPD). Methods Residents aged > 40 years old in Minhang, Shanghai, China, filled out screening questionnaires and underwent spirometry. The structured questionnaire integrating COPD population screening and COPD screening questionnaire was designed to obtain data on demographic characteristics, risk factors of COPD, respiratory symptoms, lifestyle habits, and comorbidities. We assessed the correlations between variables and COPD and the impact factors of FEV1% predicted. Results A total of 1,147 residents were included with a newly diagnosed mild to moderate COPD prevalence of 9.4% (108/1,147); half of the patients (54/108) were asymptomatic. Multivariate analysis did not reveal any significant differences in symptoms or lifestyle factors between newly diagnosed COPD patients and non-COPD participants. However, according to the generalized linear model, older age (β = −0.062, p < 0.001), male sex (β = −0.031, p = 0.047), and respiratory symptoms (β = −0.025, p = 0.013) were associated with more severe airflow limitation. Conclusion Newly diagnosed COPD patients had few differences compared with the general population, which suggests that a targeted case finding strategy other than general screening was currently preferred. More attention should be paid to respiratory symptoms when making a diagnosis and exploring new therapies and interventions for COPD in the early stage.